Association between Vitamin-D Deficiency and Knee Osteoarthritis - Afzal, Tanveer; Iqbal, Safdar; Rehman, Saif ur; Haq, Abrar-ul-; Abidin, Muhammad Zain-ul-; Aslam, Farhan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the association between vitamin-D deficiency and knee osteoarthritis. Design and Settings: It was a case-control study performed at Sir Ganga Ram Hospital Lahore over 9 months from September 2020 to May 2021. Study Procedure: This study involved 60 both male and female patients aged between 30-70 years presenting with either osteoarthritis of knee (taken as cases, n=30) or healthy attendants of patients without osteoarthritis of knee (taken as controls, n=30). Serum vitamin D level was acquired in all the study participants and vitamin D deficiency was labeled if it was ≤20ng/ml. Frequency of vitamin D deficiency was then compared between cases and controls and odds ratio was determined. An informed on paper consent was acquired from every study participant. Findings: The mean age of the patients was 52.2±10.5 years. We observed a female predominance (M:F; 1:1.4). 22 (36.7%) patients were obese while 26 (43.3%) patients belonged to middle socioeconomic class. Majority (n=33, 55.0%) of the patients had rural residence. The rate of vitamin D deficiency was considerably higher in patients with OA knee as compared to controls (70.0% vs. 16.7%; p-value<0.001; 95% CI OR=11.67). Conclusion: In the current study, we recognized statistically significant association between vitamin D deficiency and knee osteoarthritis regardless of patient’s age, gender, BMI and socioeconomic and residential status which advocates routine assessment of vitamin D among patients presenting in orthopedic outdoor so that timely identification and anticipated management of vitamin D deficiency may improve the outcome of such cases in future orthopedic practice.